Voting over type and generosity of a pension system when some individuals are myopic (2007)
This paper studies the determination through majority voting of a pension scheme when society consists of far-sighted and myopic individuals. All individuals have the same basic preferences but myopics tend to adopt a short-term view (instant gratification) when dealing with retirement saving and labor supply. Consequently, they will find themselves with low consumption after retirement and regret their insufficient savings decisions. Henceforth, when voting they tend to commit themselves into forced saving. We consider a pension scheme that is characterized by two parameters: the payroll tax rate (that determines the size or generosity of the system) and the 'Bismarckian factor' that determines its redistributiveness. Individuals vote sequentially. We examine how the introduction of myopic agents affects the generosity and the redistributiveness of the pension system. Our main result is that a flat pension system is always chosen when all individuals are of one kind (all far-sighted or all myopic), while a less redistributive system may be chosen if society is composed of both myopic and far-sighted agents. Furthermore, while myopic individuals tend to prefer larger payroll taxes than their far-sighted counterparts, the generosity of the system does not always increase with the proportion of myopics. © 2007.